Influence of different substrata on germination and growth of Vigna sinensis seedlings - Castro, Paulo R.C.; Gamero, Carlos A.; Buli, Leonardo T.; Lima, Sérgio L. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1983)
The objective of the present work was to study the effects of different substrata for germination and growth of Vigna sinensis seedlings. Treatments used were the following: castor burk + soil; castor burk + silice; xaxim + soil; xaxim + silice; sphagnum + soil; sphagnum + silice; soil; and silice, all at 1:1 proportion, in pot and bed conditions (hole). Treatments avaliation were made by determinations of the height and dry matter of the seedlings. The results showed that: (a) in the pot conditions, the best treatments were xaxim + soil; xaxim + silice and sphagnum + soil; (b) the treatments were castor burk was used the germination of Vigna seeds was impaired, and (c) the bed treatments were influenced by adjacent soil.